LKPD SISTEM PEREDARAN DARAH BERBASIS PENDEKATAN SAINTIFIK - Qurrata A’yun; Lina Arifah Fitriyah (Discovery : Jurnal Ilmu Pengetahuan, 2022)
The circulatory system is closely related to human life. In this material, students are expected to know the parts of the heart organ related to activities with the frequency of the heartbeat. Characteristics of SMP/MTs class VIII students are able to use logic so that to study the material of the circulatory system, images that represent the existence of the circulatory system are needed, namely in the form of teaching materials using a scientific approach. The use of a scientific approach in the 2013 curriculum aims to create learning according to process standards. The purpose of this study was to describe the LKPD of the circulatory system based on a scientific approach based on its validity and practicality. The method used in this research is the ADDIE development model. The data of this study consisted of data on the validity and practicality of the developed LKPD. The results showed that the LKPD of the circulatory system based on a scientific approach was declared valid and practical. Keywords: LKPD, Scientific Approaach, Circulatory System